Evolution of perioperative blood transfusion practice after coronary artery bypass grafting in the past two decades. Issue 6 (30th April 2020) - ter Woorst, Joost; Sjatskig, Jelena; Soliman‐Hamad, Mohamed; Akca, Ferdi; Haanschoten, Marco; van Straten, Albert
Abstract: Background and Aim of the Study: Transfusion of blood products after coronary artery bypass grafting (CABG) is associated with increased morbidity and mortality. We evaluated the perioperative use of blood products in patients undergoing CABG in our institution over the past two decades. Methods: The study included 18 992 patients who underwent isolated CABG at our hospital between 1998 and 2017. Baseline characteristics of patients and the number of perioperative transfusions during their hospital stay (including red blood cells [RBCs], platelets, and fresh frozen plasma [FFP]) were assessed. Logistic regression models were used to identify risk factors for perioperative transfusion. Results: The rates of perioperative RBC transfusion decreased for all patients undergoing isolated CABG (52.1% in 1998 vs 18.6% in 2017) in our institution. The mean number of transfused RBC units was significantly higher in women than in men (1.57 ± 2.2 vs 0.68 ± 1.84; P < .005); this difference remained significant over the years. After adjusting the results for other risk factors, female sex was a significant independent risk factor for perioperative RBC transfusion. The platelet transfusion rate increased over the past two decades (1.4% in 1998 vs 9.7% in 2017). The number of FFP transfusions remained unchanged. Conclusions: Over the past two decades, we observed a decrease in the incidence of perioperative RBC transfusions in patients undergoing isolated CABG, whereas platelet transfusions increased. Female sex was an independent predictor of perioperative RBC transfusion.